Kombinasi Metode (RLE) dengan Algoritma Arithmetic Coding dalam kompresi file citra - Ferdian Gowasa (PT. Ndruru Jaya Mandiri, 2025)
Abstract−When we send digital images using communication lines or the internet. With a large file size, it causes problems with sending images, namely long delivery times. Another problem is that all images require quite large storage media. This can cause quite serious problems when images are stored in a database with limited storage media. So we are trying to find a solution that can reduce the size of image files. One of the solutions to overcome the problem above is to perform compression. Image compression is the general process of minimizing the number of bits that represent an image so that the file size becomes smaller. There are two types of compression, namely lossless type and lossy type compression. Lossless type compression is compression where the quality of the compression results does not decrease when reconstructed. Meanwhile, the lossy type will result in the resulting image quality being much lower than the quality of the original image when reconstructed